Transforming schools : creating a culture of continuous improvement - Zmuda, Allison (Association for Supervision and Curriculum Development, 2004)
How can a school become a place where all members of the staff are learning, growing, and working to increase student achievement? The answer lies in systems thinking and a focus on continuous improvement, two concepts that can transform staff development from something that people merely tolerate to something that they actively pursue to create lasting improvements in teaching and learning. Each chapter of Transforming Schools: Creating a Culture of Continuous Improvement is grounded in a set of operating principles that provide practical guidance to school leaders. The story of a fictional school brings the ideas to life as the characters-a school principal, teachers, and district-level administrators-experience the shifts in thinking that are necessary to transform a school into a competent system. Through their story, the reader gains a clear understanding of the six steps of continuous improvement: 1. Identify core beliefs. 2. Create a shared vision. 3. Use data to determine gaps between the current reality and the shared vision. 4. Identify the innovations that will most likely close the gaps. 5. Develop and implement an action plan. 6. Endorse collective accountability. Thoughtful analysis of the fictional dialogue throughout the book gives readers an understanding of the dynamic nature of change, systems thinking, and continuous improvement. And questions at the end of each chapter help readers apply key concepts to their own schools. Whether your school improvement goals are clearly defined or still in development, Transforming Schools will help you tackle the many challenges of the change process.